2007 Agricultural Census Tidbit: Organic Production in Florida Is Small but Growing - Rodney L. Clouser (EDIS, 2009)
This is part of a series of five 6-8 page fact sheets by Rodney L. Clouser. It reorganizes some of the data collected in the 2007 agricultural census and offers some comments on trends and gaps in the data. Each includes references. Published by the UF Department of Food and Resource Economics, November 2009.